Socialization of Sustainable Gastronomy through Training on Strawberry (Fragaria) Processing as a Local Superfood - Nisa Utami; Sri Yuwantiningrum; Marwan Effendy; Maritza A; Zidan V (Indonesian Journal Publisher, 2025)
Sustainable food security has become an increasingly critical global issue due to rising challenges in food availability and shifts in consumption patterns. This Community Service Program (PkM) aims to enhance the capacity of Sukajadi Village community, Bogor Regency, in developing culinary products based on strawberry (Fragaria) as a local superfood through the application of Low Temperature Cooking (LTC) technology. The Methods of The program was implemented in three stages: (1) dissemination of sustainability gastronomy concepts and introduction to LTC technology, (2) hands-on training in strawberry processing to produce healthy cake products, and (3) post-training mentoring to ensure sustainable production and marketing practices. A total of 15 participants including housewives, small business owners, and local youth actively participated in the program. The Results is Organoleptic evaluation demonstrated excellent acceptance, with an average score of 4.8 across all parameters (taste, texture, appearance, and market potential). This program successfully improved the community’s knowledge and skills in local-based culinary innovation and strengthened Sukajadi Village’s potential as a sustainable culinary tourism destination.